Designing and implementing a positive body image program: Unchartered territory with a diverse team of participants. Issue 2 (June 2019) - Bailey, K Alysse; Gammage, Kimberley L; van Ingen, Cathy
This article highlights the use and importance of action research in creating a new positive body image program. The purpose of the larger action research project was to design, test, and implement a positive body image program by working with a core group of diverse stakeholders from an exercise facility. Stakeholders included older adults (aged 55+), people with physical disabilities, and those with cardiovascular disease or risk factors, populations rarely included in the body image literature, particularly in program design. The resulting program was built to teach members of the facility about body image (e.g. its definition, causes, and influences), positive body image, and how to manage their own body image experiences and be critical of the Western beauty ideal. The project is outlined with emphasis on the development of the program along with the researcher's reflexive notes and participant feedback. We also highlight the strengths and challenges of using action research in the development of a positive body image program with suggestions to improve this process for future action researchers. This research highlights the importance of using action research in order to engage participants who are not typically involved in the knowledge production process of body image program development.